Jamaica. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Jamaica during 2021 are identified, with respect to the needs and interests of the country, strengthening issues such as composting, waste management, agrotourism, food safety and health, international trade, biosafety and bioeconomy. Likewise, work was done to mitigate the effects of hidden hunger and non-communicable diseases, through biofortified crops; as well as to strengthen the production of basic grains and vegetable seeds, in the management and production of crops with resistance to antimicrobial agents. Finally, pest control was strengthened, especially against African swine fever.